Some specificities on vasculitis - Lilia Esperanza Chércoles Cazate; Juana Adela Fong Estrada (Centro Provincial de Información de Ciencias Médicas, 2016)
Vasculitis are presented in a heterogeneous group of relatively frequent clinical varieties. They are characterized by inflammation of the blood vessels, with ischemia and necrosis emergence, as well as damage of the big, medium and small vessels and, therefore, of organs or systems. Taking into account their importance and frequency in the different specialties, an exhaustive literature review was carried out where some aspects of interest related to the topic are detailed.